Analisis Penerapan Metode Demonstrasi Dalam Meningkatkan Sikap Ilmiah Siswa Pada Pembelajaran IPA Kelas 5 Ma’arif NU 01 Tangkisan Purbalingga - Dwiyani Sukmajati; Oky Ristya Trisnawati (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2026)
This study aims to analyze the application of the demonstration method to improve scientific attitudes in science learning for 5th-grade students at MI Ma’arif NU 01 Tangkisan, Purbalingga. The research approach used is descriptive qualitative, with data collected through three methods: observation and interviews. There are four sources of data in this study, namely the school principal, the 5th-grade science teacher, the 5th-grade students, and the parents of the 5th-grade students. The results of this study indicate that the application of the demonstration method in science learning has been implemented well and in accordance with its procedures. The demonstration method helps students become more actively involved in the learning process, and their skills have improved as they are able to follow experimental steps more independently and systematically. Thus, it can be concluded that the accuracy method can improve the scientific attitudes of fifth grade students in science learning.